2021
DOI: 10.1371/journal.pone.0260822
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences (ACEs) associated with reduced cognitive flexibility in both college and community samples

Abstract: The prefrontal cortex is sensitive to stress experiences and significantly impacted by early life adversity. Cognitive flexibility is an executive function that is associated with positive outcomes in adulthood and implicated in activity in the prefrontal cortex. The relationship between early life adversity and cognitive flexibility is underreported. Using the cumulative risk model, we conducted two studies to examine the association between early life adversity and cognitive flexibility in college students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…To gain more insights into the relationship between the number of ELA exposures and negative outcome expectations, scales with high internal consistency, validity, and test-retest reliability have been developed and employed in several cross-sectional studies. These studies showed that greater ELA exposure is associated with compromised cognitive flexibility, processing speed, and working memory [ 74 , 75 ]. Moreover, these negative consequences may be amplified in subjects with depression, as evidenced by smaller orbitofrontal cortex and hippocampal volumes compared to never-depressed individuals [ 74 ].…”
Section: Main Textmentioning
confidence: 99%
“…To gain more insights into the relationship between the number of ELA exposures and negative outcome expectations, scales with high internal consistency, validity, and test-retest reliability have been developed and employed in several cross-sectional studies. These studies showed that greater ELA exposure is associated with compromised cognitive flexibility, processing speed, and working memory [ 74 , 75 ]. Moreover, these negative consequences may be amplified in subjects with depression, as evidenced by smaller orbitofrontal cortex and hippocampal volumes compared to never-depressed individuals [ 74 ].…”
Section: Main Textmentioning
confidence: 99%
“…It was conducted in two colleges and public places, such as parks and malls, from two regions in Saudi Arabia. Both community‐based and college‐based samples were included because most previous studies recruited a college‐based sample (Corcoran & McNulty, 2018; Kelifa et al, 2021), which tends to be a homogenous, nonrepresentative sample in terms of ACEs exposure (Kalia et al, 2021). Thus, including community‐based and college‐based samples can mitigate the existing limitation in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…As a nonspecific, comorbid manifestation of these chronic diseases 11 13 , it is hypothesized that ACEs may also lead to anemia in older people. Furthermore, ACEs was associated with higher levels of adulthood psychological stress 14 , 15 , and the latter could subsequently lead to anemia 16 . Notably, a study showed that children with domestic violence were more likely to be anemic, suggesting that childhood psychological stress might play a role in the pathogenesis of anemia 17 .…”
Section: Introductionmentioning
confidence: 99%